A high flame-retardant composite shielding material based on modified filler
Patent Information
- Application Number
- CN202611171758.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-09
AI Technical Summary
虽然通过在基体中添加传统阻燃剂(如卤系、磷系或膨胀型阻燃剂)可在一定程度上提升材料的阻燃性能,但在复合屏蔽材料体系中,阻燃剂的引入往往面临两难困境:一方面,传统阻燃剂与聚乙烯基体的相容性较差,大量添加会进一步加剧填料的分散问题,恶化材料的力学性能;另一方面,常规共混方式添加的阻燃剂在使用过程中容易发生迁移和析出,导致阻燃效果随时间推移而逐渐衰减,无法提供持久稳定的阻燃保护
本发明通过将含磷阻燃基团与硅烷偶联剂集成为一体化改性剂,并使其在铅粉、碳化硼和纳米三氧化二铝的复合填料表面进行化学接枝,制得改性填料。当该改性填料应用于超高分子量聚乙烯/低密度聚乙烯基体中时,其表面共价连接的有机磷结构在材料受热时可原位催化聚合物成炭,形成致密阻隔层,由于阻燃组分以化学键锚定于填料表面,有效避免了传统共混体系中阻燃剂迁移析出的问题,赋予材料持久稳定的阻燃性能。同时,这种表面化学改性显著增强了填料与树脂基体间的界面结合力,使填料在基体中实现纳米尺度的均匀分散,当材料承受拉伸外力时,应力可通过牢固的界面层高效传递至刚性填料颗粒,从而明显提升材料的拉伸强度。更为关键的是,得益于改性填料优异的分散性,铅粉、碳化硼和纳米三氧化二铝各功能组分得以在基体中构建出连续且均一的屏蔽网络,克服了常规物理共混时填料易团聚、沉降而造成的屏蔽薄弱区,使材料对Cf-252源经石蜡慢化产生的热中子、Cf-252源直接发射的快中子以及60Co源释放的γ射线的削弱系数均得到显著提高,全面增强了复合材料的辐射屏蔽效能。
Smart Images

Figure REF-OBJ-1785824758469-000001 
Figure REF-OBJ-1785824758469-000002 
Figure REF-OBJ-1785824758469-000003
Abstract
Description
Technical Field
[0001] This invention belongs to the field of shielding material technology, specifically, it relates to a highly flame-retardant composite shielding material based on modified fillers. Background Technology
[0002] Radiation shielding materials have wide applications in nuclear energy, nuclear medicine, aerospace, and defense industries. In practical radiation protection scenarios, neutrons and gamma rays often coexist; therefore, an ideal shielding material needs to simultaneously possess the ability to moderate fast neutrons, absorb thermal neutrons, and attenuate gamma rays. Polyethylene, due to its high hydrogen content, can effectively moderate fast neutrons, making it an important matrix for neutron shielding materials; boron carbide has a large thermal neutron absorption cross-section, effectively absorbing thermal neutrons; and lead, with its high density and excellent attenuation properties for gamma rays, is widely used for gamma-ray shielding. Therefore, combining polyethylene with functional fillers such as lead powder and boron carbide is a common technical route for preparing materials with comprehensive neutron and gamma-ray shielding effectiveness.
[0003] However, existing polymer-based composite shielding materials still face several technical challenges that urgently need to be addressed in their application.
[0004] Firstly, functional fillers exhibit poor dispersion uniformity and are prone to agglomeration and sedimentation within the polymer matrix. Inorganic fillers such as lead powder and boron carbide differ significantly from the polyethylene matrix in terms of polarity and surface energy, resulting in poor compatibility. When these fillers are directly incorporated into the matrix using conventional physical blending methods, the filler particles are highly susceptible to agglomeration and sedimentation. This uneven dispersion not only leads to numerous stress concentration points and structural defects within the material, severely degrading its mechanical properties, but more importantly, agglomeration prevents the functional fillers from forming a continuous and uniform shielding network within the matrix, creating weak shielding channels in localized areas. This significantly reduces the material's actual shielding efficiency against neutrons and gamma rays. While some studies have attempted to improve dispersibility by using silane coupling agents to simply modify the filler surface, conventional coupling agent modification only introduces a small number of organic functional groups onto the filler surface, resulting in limited interfacial bonding strength and failing to fundamentally solve the agglomeration problem of fillers at high filler loading levels.
[0005] Secondly, the flame retardant properties of existing composite shielding materials are generally insufficient. Polyethylene itself is a flammable polymer with a low limiting oxygen index. Once a fire occurs, it will burn rapidly and release a large amount of heat and smoke, seriously threatening personnel safety and equipment operation. Although adding traditional flame retardants (such as halogenated, phosphorus-based, or intumescent flame retardants) to the matrix can improve the flame retardant properties of the material to some extent, the introduction of flame retardants in composite shielding material systems often faces a dilemma: on the one hand, traditional flame retardants have poor compatibility with the polyethylene matrix, and adding large amounts will further aggravate the dispersion problem of fillers and deteriorate the mechanical properties of the material; on the other hand, flame retardants added by conventional blending methods are prone to migration and precipitation during use, causing the flame retardant effect to gradually decay over time, failing to provide long-lasting and stable flame retardant protection.
[0006] Third, existing technologies struggle to simultaneously optimize shielding performance, mechanical properties, and flame retardant properties. Shielding requires high filler volumes of heavy inorganic fillers such as lead powder and boron carbide, but high filler volumes inevitably lead to decreased material toughness and processing difficulties. Improving dispersibility requires the introduction of interface modifiers, but conventional modifiers lack flame retardant properties. Enhancing flame retardancy requires the addition of additional flame retardants, which may exacerbate interfacial compatibility issues. These three aspects are subject to complex interrelationships. Achieving highly uniform filler dispersion, significantly improved flame retardant properties, and effectively enhanced radiation shielding efficiency without significantly sacrificing mechanical and processing properties is a critical technological bottleneck that urgently needs to be overcome in the field of polymer-based composite shielding materials.
[0007] To address the shortcomings of the existing technologies, this invention provides a highly flame-retardant composite shielding material based on modified fillers, aiming to achieve a synergistic solution to the aforementioned problems through the design of an integrated modifier. Summary of the Invention
[0008] The purpose of this invention is to overcome the shortcomings of the prior art and provide a highly flame-retardant composite shielding material based on modified fillers.
[0009] The objective of this invention can be achieved through the following technical solutions: A highly flame-retardant composite shielding material based on modified filler comprises the following components: by weight, 40-50 parts ultra-high molecular weight polyethylene, 10-20 parts low-density polyethylene, 0.3-1 parts antioxidant, 1-2 parts lubricant, and 25-35 parts modified filler; wherein the modified filler is a composite particle of lead powder, boron carbide, and nano-alumina modified by a modifier.
[0010] In a more optimized manner, the preparation process of the modified filler is as follows: S1: Diphenylphosphine oxide was added to xylene and stirred until homogeneous to obtain a diphenylphosphine oxide solution. Itaconic acid was added to 1,4-dioxane and stirred until homogeneous. Itaconic acid was then slowly added dropwise to the diphenylphosphine oxide solution at room temperature. After the addition was complete, the temperature was raised to 100°C and the reaction was carried out at a constant temperature with continuous stirring for 9 hours. After the reaction was completed, the mixture was cooled to room temperature and the solvent was removed by rotary evaporation. The solid after evaporation was then ground, washed, and dried to obtain intermediate A. S2: Intermediate A was added to anhydrous N,N-dimethylformamide and stirred until homogeneous. Then, dicyclohexylcarbodiimide and 4-dimethylaminopyridine were added sequentially and stirred until completely dissolved. Subsequently, 3-aminopropyltriethoxysilane solution was slowly added dropwise under ice bath cooling. After the addition was complete, the ice bath was removed and the reaction was continued to be stirred at room temperature for 12 hours. After the reaction was completed, the mixture was filtered, and the filtrate was slowly added dropwise to a large amount of anhydrous diethyl ether under stirring. A solid precipitated out, which was then filtered, washed with anhydrous diethyl ether, and dried under vacuum to obtain the modifier. S3: Lead powder, boron carbide, and nano-alumina were added to a mixed solvent of anhydrous ethanol and deionized water. After ultrasonic dispersion, the pH was adjusted to 4-5 with acetic acid to obtain a mixed suspension. The modifier was dissolved in anhydrous ethanol, stirred evenly, and then slowly added dropwise to the mixed suspension at room temperature. After the addition was complete, the temperature was raised to 60°C and the reaction was carried out with constant temperature and stirring for 4 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed successively with anhydrous ethanol and deionized water, and vacuum dried to obtain the modified filler.
[0011] First, the phosphorus-hydrogen bond in diphenylphosphine oxide undergoes a nucleophilic addition reaction with the carbon-carbon double bond in itaconic acid under heating conditions, generating intermediate A. This step introduces the organophosphorus flame-retardant structure into the intermediate molecule. Subsequently, the carboxyl group in intermediate A undergoes an amidation condensation reaction with the amino group in 3-aminopropyltriethoxysilane under the dehydration of dicyclohexylcarbodiimide and the catalysis of 4-dimethylaminopyridine. The carboxyl group loses its hydroxyl group, and the amino group loses its hydrogen atom to form an amide bond, thereby covalently linking the silane coupling agent fragment to the phosphorus-containing intermediate, resulting in a modifier with both an organophosphorus structure and a hydrolyzable ethoxysilyl group. Finally, in an ethanol-water mixture adjusted to a weakly acidic state with acetic acid, the ethoxysilyl group at the end of the modifier molecule hydrolyzes to generate silanol groups. These silanol groups undergo a dehydration condensation reaction with the hydroxyl groups on the surfaces of three inorganic fillers: lead powder, boron carbide, and nano-alumina, forming Si-OM covalent bonds, ultimately achieving chemical grafting of the modifier onto the surface of the inorganic fillers.
[0012] The structure of the modifier is shown below:
[0013] In a more optimized manner, the raw materials for preparing intermediate A include the following components: by weight, 10-12 parts diphenylphosphine oxide, 40-50 parts xylene, 6-7 parts itaconic acid, and 30-40 parts 1,4-dioxane.
[0014] More preferably, the raw materials for preparing the modifier include the following components: by weight, 10-12 parts of intermediate A, 50-60 parts of anhydrous N,N-dimethylformamide, 12-13 parts of dicyclohexylcarbodiimide, 1-2 parts of 4-dimethylaminopyridine, and 25-30 parts of 3-aminopropyltriethoxysilane solution; wherein the concentration of the 3-aminopropyltriethoxysilane solution is 50 wt%.
[0015] In a more optimized manner, the raw materials for preparing the modified filler include the following components: by weight, 20-25 parts lead powder, 4-5 parts boron carbide, 1-2 parts nano aluminum oxide, 1-2 parts modifier, 100-120 parts anhydrous ethanol, and 30-40 parts deionized water.
[0016] More preferably, the antioxidant is antioxidant 1010.
[0017] Ideally, the lubricant is zinc stearate.
[0018] Ideally, the lead powder has a particle size of 10-30 μm; the boron carbide has a particle size of 2-10 μm; and the nano-alumina has a particle size of 10-30 nm.
[0019] The beneficial effects of this invention are: This invention integrates phosphorus-containing flame-retardant groups with a silane coupling agent into a single modifier, and then chemically grafts this modifier onto the surface of a composite filler composed of lead powder, boron carbide, and nano-alumina to obtain a modified filler. When this modified filler is applied to an ultra-high molecular weight polyethylene / low-density polyethylene matrix, its surface-covalently linked organophosphorus structure can catalyze the polymer to carbonization in situ when the material is heated, forming a dense barrier layer. Because the flame-retardant components are chemically anchored to the filler surface, the problem of flame retardant migration and precipitation in traditional blending systems is effectively avoided, giving the material durable and stable flame-retardant properties. Simultaneously, this surface chemical modification significantly enhances the interfacial bonding force between the filler and the resin matrix, enabling uniform nanoscale dispersion of the filler within the matrix. When the material is subjected to tensile forces, the stress can be efficiently transferred to the rigid filler particles through the robust interfacial layer, thereby significantly improving the tensile strength of the material. More importantly, thanks to the excellent dispersibility of the modified filler, the functional components of lead powder, boron carbide and nano-alumina can form a continuous and uniform shielding network in the matrix. This overcomes the weak shielding areas caused by the easy agglomeration and sedimentation of fillers during conventional physical blending. As a result, the attenuation coefficients of the material for thermal neutrons generated by Cf-252 source moderated by paraffin, fast neutrons directly emitted by Cf-252 source and γ-rays released by 60Co source are significantly improved, thus comprehensively enhancing the radiation shielding effectiveness of the composite material. Detailed Implementation
[0020] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0021] Example 1: A method for preparing a highly flame-retardant composite shielding material based on modified fillers, comprising the following steps: Step 1: Mix 40 parts of ultra-high molecular weight polyethylene, 10 parts of low-density polyethylene, 0.3 parts of antioxidant (antioxidant 1010), 1 part of lubricant (zinc stearate), and 25 parts of modified filler, and stir evenly to obtain composite powder. Step 2: Fill the composite powder into the steel mold, place it in the hot press, and hot press it (temperature 170℃, pressure 10MPa, time 100min). Then, maintain the mold closing pressure and introduce cooling medium to cold press and shape it. After cooling, demold to obtain the composite shielding material. The preparation process of the modified filler is as follows: S1: Add 10 parts of diphenylphosphine oxide to 40 parts of xylene and stir until homogeneous to obtain a diphenylphosphine oxide solution; add 6 parts of itaconic acid to 30 parts of 1,4-dioxane and stir until homogeneous, then slowly add it dropwise to the diphenylphosphine oxide solution at room temperature. After the addition is complete, raise the temperature to 100℃ and stir continuously at a constant temperature for 9 hours. After the reaction is complete, cool to room temperature and remove the solvent by rotary evaporation. Then grind the evaporated solid, wash and dry it to obtain intermediate A. S2: Add 10 parts of intermediate A to 50 parts of anhydrous N,N-dimethylformamide, stir until homogeneous, then add 12 parts of dicyclohexylcarbodiimide and 1 part of 4-dimethylaminopyridine, stirring until completely dissolved; then, under ice bath cooling, slowly add 25 parts of 3-aminopropyltriethoxysilane solution (concentration 50wt%), after which remove the ice bath and continue stirring at room temperature for 12 hours; after the reaction is complete, filter, and slowly add the filtrate to a large amount of anhydrous diethyl ether under stirring, precipitating a solid, filter, wash with anhydrous diethyl ether, and vacuum dry to obtain the modifier; S3: 20 parts lead powder (particle size 10 μm), 4 parts boron carbide (particle size 10 μm) and 1 part nano aluminum oxide (particle size 10 nm) were added to a mixed solvent of 50 parts anhydrous ethanol and 30 parts deionized water. After ultrasonic dispersion, the pH was adjusted to 4-5 with acetic acid to obtain a mixed suspension. 1 part modifier was dissolved in 50 parts anhydrous ethanol and stirred evenly. It was then slowly added dropwise to the mixed suspension at room temperature. After the addition was complete, the temperature was raised to 60℃ and the reaction was carried out with constant temperature and stirring for 4 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed successively with anhydrous ethanol and deionized water, and vacuum dried to obtain the modified filler.
[0022] Example 2: A method for preparing a highly flame-retardant composite shielding material based on modified fillers, comprising the following steps: Step 1: Mix 50 parts of ultra-high molecular weight polyethylene, 20 parts of low-density polyethylene, 1 part of antioxidant (antioxidant 1010), 2 parts of lubricant (zinc stearate), and 35 parts of modified filler, and stir evenly to obtain composite powder. Step 2: Fill the composite powder into the steel mold, place it in the hot press, and hot press it (temperature 170℃, pressure 10MPa, time 100min). Then, maintain the mold closing pressure and introduce cooling medium to cold press and shape it. After cooling, demold to obtain the composite shielding material. The preparation process of the modified filler is as follows: S1: 12 parts of diphenylphosphine oxide were added to 50 parts of xylene and stirred until homogeneous to obtain a diphenylphosphine oxide solution; 7 parts of itaconic acid were added to 40 parts of 1,4-dioxane and stirred until homogeneous, and then slowly added dropwise to the diphenylphosphine oxide solution at room temperature. After the addition was complete, the temperature was raised to 100℃ and the reaction was carried out at a constant temperature with continuous stirring for 9 hours. After the reaction was completed, the temperature was cooled to room temperature, and the solvent was removed by rotary evaporation. The solid after evaporation was then ground, washed, and dried to obtain intermediate A. S2: Add 12 parts of intermediate A to 60 parts of anhydrous N,N-dimethylformamide, stir until homogeneous, then add 13 parts of dicyclohexylcarbodiimide and 2 parts of 4-dimethylaminopyridine, stirring until completely dissolved; then, under ice bath cooling, slowly add 30 parts of 3-aminopropyltriethoxysilane solution (concentration 50wt%), after which remove the ice bath and continue stirring at room temperature for 12 hours; after the reaction is complete, filter, and slowly add the filtrate to a large amount of anhydrous diethyl ether under stirring, precipitating a solid, filter, wash with anhydrous diethyl ether, and vacuum dry to obtain the modifier; S3: 25 parts lead powder (particle size 10 μm), 5 parts boron carbide (particle size 10 μm) and 2 parts nano aluminum oxide (particle size 10 nm) were added to a mixed solvent of 60 parts anhydrous ethanol and 40 parts deionized water. After ultrasonic dispersion, the pH was adjusted to 4-5 with acetic acid to obtain a mixed suspension. 2 parts modifier were dissolved in 60 parts anhydrous ethanol and stirred evenly. The mixture was then slowly added dropwise to the mixed suspension at room temperature. After the addition was complete, the temperature was raised to 60°C and the reaction was carried out with constant temperature and stirring for 4 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed successively with anhydrous ethanol and deionized water, and vacuum dried to obtain the modified filler.
[0023] Example 3: A method for preparing a highly flame-retardant composite shielding material based on modified fillers, comprising the following steps: Step 1: Mix 45 parts of ultra-high molecular weight polyethylene, 15 parts of low-density polyethylene, 0.65 parts of antioxidant (antioxidant 1010), 1.5 parts of lubricant (zinc stearate), and 30 parts of modified filler, and stir evenly to obtain composite powder. Step 2: Fill the composite powder into the steel mold, place it in the hot press, and hot press it (temperature 170℃, pressure 10MPa, time 100min). Then, maintain the mold closing pressure and introduce cooling medium to cold press and shape it. After cooling, demold to obtain the composite shielding material. The preparation process of the modified filler is as follows: S1: 11 parts of diphenylphosphine oxide were added to 45 parts of xylene and stirred until homogeneous to obtain a diphenylphosphine oxide solution; 6.5 parts of itaconic acid were added to 35 parts of 1,4-dioxane and stirred until homogeneous, and then slowly added dropwise to the diphenylphosphine oxide solution at room temperature. After the addition was complete, the temperature was raised to 100℃ and the reaction was carried out at a constant temperature with continuous stirring for 9 hours. After the reaction was completed, the temperature was cooled to room temperature, and the solvent was removed by rotary evaporation. The solid after evaporation was then ground, washed, and dried to obtain intermediate A. S2: 11 parts of intermediate A were added to 55 parts of anhydrous N,N-dimethylformamide and stirred until homogeneous. Then, 12.5 parts of dicyclohexylcarbodiimide and 1.5 parts of 4-dimethylaminopyridine were added sequentially and stirred until completely dissolved. Subsequently, under ice bath cooling, 27.5 parts of 3-aminopropyltriethoxysilane solution (concentration of 50wt%) were slowly added dropwise. After the addition was completed, the ice bath was removed and the reaction was continued to be stirred at room temperature for 12 hours. After the reaction was completed, the mixture was filtered, and the filtrate was slowly added dropwise to a large amount of anhydrous diethyl ether under stirring. The solid precipitated, filtered, washed with anhydrous diethyl ether, and dried under vacuum to obtain the modifier. S3: 22.5 parts lead powder (particle size 10 μm), 4.5 parts boron carbide (particle size 10 μm), and 1.5 parts nano-alumina (particle size 10 nm) were added to a mixed solvent of 55 parts anhydrous ethanol and 35 parts deionized water. After ultrasonic dispersion, the pH was adjusted to 4-5 with acetic acid to obtain a mixed suspension. 1.5 parts modifier were dissolved in 55 parts anhydrous ethanol and stirred evenly. The mixture was then slowly added dropwise to the mixed suspension at room temperature. After the addition was complete, the temperature was raised to 60°C and the reaction was carried out with constant temperature and stirring for 4 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed successively with anhydrous ethanol and deionized water, and vacuum dried to obtain the modified filler.
[0024] Comparative Example 1: Modification of lead powder, boron carbide, and nano-alumina using only 3-aminopropyltriethoxysilane, as detailed below: Step 1: Mix 45 parts of ultra-high molecular weight polyethylene, 15 parts of low-density polyethylene, 0.65 parts of antioxidant (antioxidant 1010), 1.5 parts of lubricant (zinc stearate), and 30 parts of modified filler, and stir evenly to obtain composite powder. Step 2: Fill the composite powder into the steel mold, place it in the hot press, and hot press it (temperature 170℃, pressure 10MPa, time 100min). Then, maintain the mold closing pressure and introduce cooling medium to cold press and shape it. After cooling, demold to obtain the composite shielding material. The preparation process of the modified filler is as follows: 22.5 parts of lead powder (particle size 10 μm), 4.5 parts of boron carbide (particle size 10 μm), and 1.5 parts of nano-alumina (particle size 10 nm) were added to a mixed solvent of 55 parts anhydrous ethanol and 35 parts deionized water. After ultrasonic dispersion, the pH was adjusted to 4-5 with acetic acid to obtain a mixed suspension. 10 parts of 3-aminopropyltriethoxysilane solution (concentration 50 wt%) were stirred evenly and then slowly added dropwise to the mixed suspension at room temperature. After the addition was complete, the temperature was raised to 60 °C and the reaction was carried out with constant temperature and stirring for 4 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed successively with anhydrous ethanol and deionized water, and vacuum dried to obtain the modified filler.
[0025] Testing Experiment (I): The composite shielding materials obtained in the examples and comparative examples were prepared into corresponding samples according to different testing standards, and relevant tests were conducted: (1) The oxygen index was determined according to the national standard GB / T2406.2-2009; (2) Tensile strength was determined according to national standard GB / T 1040.2-2022; The obtained data is shown in Table 1: Table 1
[0026] Test (II): The composite shielding materials obtained in the examples and comparative examples were made into corresponding samples with a thickness of 25 mm according to different test standards, and relevant tests were carried out at room temperature: (1) Thermal neutron shielding performance test A thermal neutron field was generated using a Cf-252 neutron source through a 12 cm thick paraffin moderation layer, employing LND Corporation. 3 He proportional counters are used to determine the thermal neutron shielding efficiency of materials (characterized by attenuation coefficients). (2) Fast neutron shielding performance test Fast neutrons emitted directly from the Cf-252 neutron source, through 3 He counters are used to quantitatively analyze the attenuation ability of materials for fast neutrons; (3) Gamma-ray shielding performance test use 60 The gamma rays emitted by the Co radioactive source were used in conjunction with a NaI crystal detector to accurately measure the material's shielding effectiveness against gamma radiation (expressed as attenuation coefficient); the data obtained are shown in Table 2. Table 2
[0027] Conclusion: The test data in Tables 1 and 2 clearly show that the high flame-retardant composite shielding material based on modified filler provided by this invention exhibits significant technical advantages in terms of mechanical properties, flame-retardant properties, and radiation shielding performance. Regarding tensile strength, Examples 1 to 3 achieved 24.5 MPa, 24.8 MPa, and 25.6 MPa, respectively, all significantly better than the 21.2 MPa of Comparative Example 1. Regarding limiting oxygen index, Examples 1 to 3 had 27.5%, 28.1%, and 28.5%, respectively, all far exceeding the 22.4% of Comparative Example 1. Regarding radiation shielding performance, the thermal neutron attenuation coefficients of Examples 1 to 3 were 2.75, 2.95, and 3.10, the fast neutron attenuation coefficients were 1.64, 1.75, and 1.81, and the γ-radiation attenuation coefficients were 1.88, 2.01, and 2.12, respectively. All three shielding performance indicators showed a trend where Example 3 was superior to Example 2, which was superior to Example 1, which was superior to Comparative Example 1. The above data fully demonstrates that this invention, through the chemical grafting of an integrated modifier onto the surface of inorganic fillers, introduces organophosphorus structures and silane coupling agent fragments, effectively enhancing the interfacial bonding between the filler and the matrix. This avoids the problem of flame retardant migration and precipitation in traditional blending systems, while simultaneously endowing the material with durable and stable flame retardant properties. Furthermore, it enables the functional components of lead powder, boron carbide, and nano-alumina to construct a continuous and uniform shielding network within the matrix, overcoming the weak shielding areas caused by filler agglomeration and sedimentation during conventional physical blending. Further comparison of the three embodiments shows that Embodiment 3 achieves the best performance in all aspects, making it the optimal implementation scheme of this invention. Comparative Embodiment 1, due to the use of only ordinary silane coupling agents for modification, lacks organophosphorus flame retardant structures and has weaker interfacial bonding, resulting in significantly inferior performance compared to the embodiment. In summary, this invention, through surface chemical grafting of a composite filler with an integrated modifier, simultaneously achieves multiple technical effects such as interface enhancement, flame retardancy improvement, and shielding network optimization, fully demonstrating the advanced nature and practicality of the technical solution of this invention.
[0028] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0029] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.
Claims
1. A highly flame-retardant composite shielding material based on modified fillers, characterized in that, It comprises the following components by weight: 40-50 parts ultra-high molecular weight polyethylene, 10-20 parts low-density polyethylene, 0.3-1 parts antioxidant, 1-2 parts lubricant, and 25-35 parts modified filler; wherein the modified filler is a composite particle of lead powder, boron carbide, and nano-alumina modified by a modifier.
2. The highly flame-retardant composite shielding material based on modified filler according to claim 1, characterized in that, The preparation process of the modified filler is as follows: S1: Diphenylphosphine oxide was added to xylene and stirred until homogeneous to obtain a diphenylphosphine oxide solution. Itaconic acid was added to 1,4-dioxane and stirred until homogeneous. Itaconic acid was then slowly added dropwise to the diphenylphosphine oxide solution at room temperature. After the addition was complete, the temperature was raised to 100°C and the reaction was carried out at a constant temperature with continuous stirring for 9 hours. After the reaction was completed, the mixture was cooled to room temperature and the solvent was removed by rotary evaporation. The solid after evaporation was then ground, washed, and dried to obtain intermediate A. S2: Intermediate A was added to anhydrous N,N-dimethylformamide and stirred until homogeneous. Then, dicyclohexylcarbodiimide and 4-dimethylaminopyridine were added sequentially and stirred until completely dissolved. Subsequently, 3-aminopropyltriethoxysilane solution was slowly added dropwise under ice bath cooling. After the addition was complete, the ice bath was removed and the reaction was continued to be stirred at room temperature for 12 hours. After the reaction was completed, the mixture was filtered, and the filtrate was slowly added dropwise to a large amount of anhydrous diethyl ether under stirring. A solid precipitated out, which was then filtered, washed with anhydrous diethyl ether, and dried under vacuum to obtain the modifier. S3: Lead powder, boron carbide, and nano-alumina were added to a mixed solvent of anhydrous ethanol and deionized water. After ultrasonic dispersion, the pH was adjusted to 4-5 with acetic acid to obtain a mixed suspension. The modifier was dissolved in anhydrous ethanol, stirred evenly, and then slowly added dropwise to the mixed suspension at room temperature. After the addition was complete, the temperature was raised to 60°C and the reaction was carried out with constant temperature and stirring for 4 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed successively with anhydrous ethanol and deionized water, and vacuum dried to obtain the modified filler.
3. The highly flame-retardant composite shielding material based on modified filler according to claim 2, characterized in that, The raw materials for preparing intermediate A include the following components: by weight, 10-12 parts diphenylphosphine oxide, 40-50 parts xylene, 6-7 parts itaconic acid, and 30-40 parts 1,4-dioxane.
4. The highly flame-retardant composite shielding material based on modified filler according to claim 2, characterized in that, The raw materials for preparing the modifier include the following components: by weight, 10-12 parts intermediate A, 50-60 parts anhydrous N,N-dimethylformamide, 12-13 parts dicyclohexylcarbodiimide, 1-2 parts 4-dimethylaminopyridine, and 25-30 parts 3-aminopropyltriethoxysilane solution; wherein the concentration of the 3-aminopropyltriethoxysilane solution is 50 wt%.
5. A highly flame-retardant composite shielding material based on modified filler according to claim 2, characterized in that, The raw materials for preparing the modified filler include the following components: by weight, 20-25 parts lead powder, 4-5 parts boron carbide, 1-2 parts nano aluminum oxide, 1-2 parts modifier, 100-120 parts anhydrous ethanol, and 30-40 parts deionized water.
6. The highly flame-retardant composite shielding material based on modified filler according to claim 1, characterized in that, The antioxidant is antioxidant 1010.
7. The highly flame-retardant composite shielding material based on modified filler according to claim 1, characterized in that, The lubricant is zinc stearate.
8. The highly flame-retardant composite shielding material based on modified filler according to claim 1, characterized in that, The lead powder has a particle size of 10-30 μm; the boron carbide has a particle size of 2-10 μm; and the nano-alumina has a particle size of 10-30 nm.